Foundation and Earth - Asimov, Isaac, 1920-1992 (Asimov, Isaac, 1920-1992. Foundation trilogy, 2020)
The fifth novel in Asimov's popular Foundation series opens with second thoughts. Councilman Golan Trevize is wondering if he was right to choose a collective mind as the best possible future for humanity over the anarchy of contentious individuals, nations and planets. To test his conclusion, he decides he must know the past and goes in search of legendary Earth, all references to which have been erased from galactic libraries. The societies encountered along the way become arguing points in a book-long colloquy about man's fate, conducted by Trevize and traveling companion Bliss, who is part of the first world/mind, Gaia.